Increasing understanding of foreign language vocabulary through technology-based educational games - Pertiwi, Anggun; Danial, Haris; Maharani Asnur, Sardian; Abdullah, Dahlan (International Journal of Language and Ubiquitous Learning, 2023)
Background. In the 21st century learning era, innovation in learning methods is crucial. Educational games stand out as an interesting and effective solution to improve the quality of learning. In particular, foreign language learning requires a more interactive and fun approach to motivate students. Purpose. The main aim of this research is to measure the extent to which technology-based educational games can improve understanding of foreign language vocabulary. In addition, this research evaluates the level of satisfaction and motivation of students in using educational games as a means of learning vocabulary. Method. With a quantitative approach and survey design, this research involved 30 language students. The use of the method of drawing student numbers for sample selection and distributing the questionnaire link via the WhatsApp group with a random technique ensures representativeness and voluntary participation of respondents. The research instrument was a structured questionnaire. Results. The results of the questionnaire showed that 70% of respondents expressed satisfaction with the use of educational games, with 30% of them feeling 'Very Satisfied.' In terms of motivation, 87% of respondents reported increased motivation after using educational games, where 30% said 'Very Improved' and 56.7% said 'Improved.' Even though 13.3% of respondents felt 'Neutral' regarding increasing motivation, this does not reduce the positive impact felt by the majority of participants. Conclusion. The use of educational games is effective in increasing student satisfaction and motivation in learning foreign language vocabulary. The game's attractiveness factors, reward system, and level achievement are the main contributors to a positive experience. Variations in levels of satisfaction and motivation can be used as a basis for further development and optimization of educational game designs according to student preferences and expectations. This conclusion provides a basis for improving the quality of foreign language learning at the tertiary level.